Profil Penulisan Catatan Perkembangan Pasien Terintegrasi (CPPT) Apoteker Di Instalasi Rawat Inap (IRNA) Non Bedah Di Rsup Dr. M. Djamil Padang - Sara Surya; Hansen Nasif; Susti Upadayani (LPPM Universitas Dharma Andalas, 2022)
Integrated Patient Development Record (CPPT) is documentation between professions providing nursing care regarding integrated patient development in the form of patient medical records, which functions to improve the quality of communication between professions at the hospital. In this medical record data contains SOAP data (subjective, objective, assessment, Plan). This study aims to study the analysis of the completeness of writing integrated patient progress notes by pharmacists in the Non-Surgical Inpatient Installation (IRNA) room of Dr. M. Djamil Padang. This research is a descriptive analytical research with retrospective approach and data collection. Data collection system is random sampling. The sampling technique used is the raosoft calculator, the total population obtained was 8,190 populations, 367 medical record data were collected for analysis, taken every 5th, 10th, 15th, 20th. The observed data was taken from January 1, 2019 to December 31, 2019. In this research, the results of the analysis of the completeness of the pharmacist's CPPT writing were 270 pharmacist CPPT data (74%) which were written completely from the 367 pharmacists' CPPT analyzed, and 97 pharmacist CPPT data (26%) which were written incomplete from the 367 pharmacist CPPT data analyzed.